Overseas aid : its defence and reform - Mosley, Paul (Great Britain : Wheatsheaf Books, 1987)
The book discusses the effectiveness of aid in relation to both its impact on production in developing countries and also in relation to the objective of reaching the poorest people.
Includes index
Bibliography p.243-257
usc 24/09/2018
Loans
Keywords: Economic assistance; Developing countries